Martin Luther and Women - Wilson, Sarah Hinlicky (Vox Scripturae - Revista Teológica Internacional, 2018)
This essay offers an overview of Martin Luther’s view of women with special attention to his illegal will in favor of his wife and his discussion of men and women in the late Genesis commentary. It then considers three women who responded to Luther’s reforms and lived out their Christian faith accordingly: Katharina von Bora, Elisabeth Cruciger, and Argula von Grumbach, tracing in particular their private or public roles in expressing their faith.